Determination of Fever Management and Rational Drug Use of Mothers with Children Under Six Years Old: Fever management and rational drug use of mothers - Karakul, Atiye; Doğan, Pınar (Health & Research Journal, 2022)
Background: Fever is one of the most common problems of childhood, which worries mothers. An insufficient level of knowledge about when and how to intervene in fever causes children to be exposed to inadequate and/or wrong practices and to use unnecessary or improper doses of antipyretics and antibiotics Aim: In this study, it was aimed to examine the fever management and rational drug use of mothers with children under six years old. Material and Method: The research is of descriptive type. It was conducted with 276 mothers between January and March 2021.Introductory Information Form, Parental Fever Management Scale (PFMS) and Rational Drug Use Scale (RDUS) were used. The data were analyzed by number and percentage distribution, mean standard deviation, Mann Whitney U and Kruskal-Wallis and correlation test. Results: It was determined that 25% of the mothers participating in the study were 30 years old and younger. The mean total score for PFMS is 28.71±3.86; RDU scale is 39.28±3.18. There was a statistically significant difference between the mothers taking their children to the doctor to fever, the children being hospitalized due to high fever before, the children having convulsions due to fever, and measuring the fever of the children when they got a fever, and the total score of the parental fever management scale. It was found that there was a statistically significant difference between the education level of the mothers, the place of residence, income level, and the total score of the rational drug use scale and getting information from someone when fever occurred. Conclusion: Based on the result of this study, It was determined that the mothers had good fever management and had rational knowledge of drug use. In addition, mothers' education level, place of residence, income level and the fact that they receive information from someone during febricity increase the knowledge of rational drug use. Therefore, it can be suggested that education programs for mothers on fever management and rational drug use.